2009
DOI: 10.1243/09544119jeim485
|View full text |Cite
|
Sign up to set email alerts
|

Stress analysis in the mandibular condyle during prolonged clenching: A theoretical approach with the finite element method

Abstract: Parafunctional habits, such as bruxism and prolonged clenching, have been associated with functional overloading in the temporomandibular joint (TMJ), which may result in internal derangement and osteoarthrosis of the TMJ. In this study, the distributions of stress on the mandibular condylar surface during prolonged clenching were examined with TMJ mathematical models. Finite element models were developed on the basis of magnetic resonance images from two subjects with or without anterior disc displacement of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 37 publications
1
20
1
1
Order By: Relevance
“…[39] also used morning orofacial jaw muscle fatigue to diagnose SB. It has been shown that mandibular condyle is displaced and TMJ stress is increased by the occlusal force [40-43]. Baba et al .…”
Section: Discussionmentioning
confidence: 99%
“…[39] also used morning orofacial jaw muscle fatigue to diagnose SB. It has been shown that mandibular condyle is displaced and TMJ stress is increased by the occlusal force [40-43]. Baba et al .…”
Section: Discussionmentioning
confidence: 99%
“…Another benefit of the subtotal replacement is possibility of use before of the end of facial skeletal system growth [6]. The stress-strain analyses of TMJ and TMJP based on several numerical models and methods, namely the finite element method, were studied by several authors [13,15,1,7,9]. For these analyses the special software is also used [12,14].…”
Section: Tmj Implant Devicesmentioning
confidence: 99%
“…To approach this problem, finite element models were established on the basis of magnetic resonance images from two subjects with or without anterior disc displacement of the TMJ [25,26]. The stress values after a 10-min clenching varied from 20 to 100 kPa according to the different sites of condylar cartilage [25,26]. It was also shown that rabbit chondrocytes subjected to stress ranging from 0 to 200 kPa yielded tissue-engineered cartilage of the best quality [27].…”
Section: Discussionmentioning
confidence: 99%